Safety of Cosmetic Procedures in Elderly and Octogenarian Patients. (24th April 2015) - Yeslev, Max; Gupta, Varun; Winocour, Julian; Shack, R. Bruce; Grotting, James C.; Higdon, K. Kye
Abstract : Background: The proportion of elderly patients in North America is increasing. This has resulted in an increased number of elderly patients undergoing cosmetic procedures. Objectives: The purpose of this study was to determine the incidence of postoperative complications in elderly patients (age ≥65) undergoing elective aesthetic plastic surgical procedures compared with younger patients. Methods: A total of 183, 914 cosmetic surgical procedures were reviewed using the prospectively enrolled cohort of patients in the CosmetAssure database. Comorbidities and postoperative complications in elderly and younger patient groups were recorded and compared. A separate analysis of postoperative complications was performed in the octogenarian subgroup (age ≥80). Results: A total of 6786 elderly patients who underwent cosmetic procedures were included in the study. Mean ages (±standard deviation) in elderly and younger patients were 69.1 ± 4.1 and 39.2 ± 12.5 years, respectively. The elderly patient population had more men, a higher mean body mass index (BMI), a higher prevalence of diabetes mellitus (DM), and fewer smokers compared with the younger patients. The overall postoperative complication rate was not significantly different between elderly and younger patients. When stratified by type of cosmetic procedure, only abdominoplasty was associated with a higher postoperative complication rate in elderly compared with younger patients. The most common postoperative complications in elderly patients were hematoma and infection. The overall postoperative complication rate in octogenarians was 2.2%, which was not significantly different from the younger population. Conclusions: Cosmetic procedures in elderly patients, including octogenarians, remain safe with an acceptable complication rate compared to younger patients. Level of Evidence: 3 Risk